An evaluation of the Ateneo de Manila University archives a user study - Gapan, Andrea Denise S. (School of Library and Information Studies, University of the Philippines, 2016)
Archives have a different priority compared to libraries. Their main task is to preserve documents for access. However, there is a need to conduct user studies in order to evaluate its resources, services and facilities. Through the user's perspective, the archives can see if it satisfies their information needs.